A SEPTIC MASQUERADE: MULTIFOCAL SEPTIC ARTHRITIS REVEALING DISSEMINATED MELIOIDOSIS IN A YOUNG PATIENT WITH TYPE 1 DIABETES - Rasidi, Nur Iffah Illani Mohamed; Puah, Soo Huan; Lee, Wei Ping; Poh Shean, Poh Shean; Azizan, Fauzi (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Melioidosis, caused by Burkholderia pseudomallei, is a potentially fatal infection endemic to Southeast Asia and northern Australia. While often linked to type 2 diabetes mellitus, disseminated melioidosis in patients with type 1 diabetes mellitus (T1DM) is exceedingly rare, more so if with musculoskeletal involvement. We report a case of disseminated melioidosis presenting with multifocal septic arthritis, a thigh abscess, pulmonary infection, and splenic microabscesses in an adolescent with T1DM, highlighting the need for heightened vigilance in endemic regions. CASE An 18-year-old Indian female with T1DM since age 13 (HbA1c 10.3%), on insulin aspart and detemir, presented with five weeks of fever, one week of painful left thigh swelling, and three days of cough. She was admitted with severe diabetic ketoacidosis and was empirically treated with intravenous ampicillin-sulbactam. Ultrasound of the left thigh revealed an abscess, which was drained; pus culture was positive for Burkholderia pseudomallei. Antibiotics were escalated to intravenous ceftazidime and trimethoprim-sulfamethoxazole. Despite treatment, she remained febrile and required intubation on day eight of admission due to respiratory compromise. Blood and respiratory cultures also isolated Burkholderia pseudomallei. Computed tomography of the thorax, abdomen, and pelvis showed pulmonary infection (patchy ground-glass opacities, bilateral consolidation, minimal pleural effusion) and splenic microabscesses. Joint ultrasound revealed bilateral knee effusions and a complex right ankle effusion. Emergency arthrotomies and washouts of all affected joints yielded the same organism. Her fever resolved with marked clinical improvement following complete source clearance. She was discharged ambulatory after six weeks of intravenous ceftazidime and a five-month oral eradication course, with optimized glycemic control. Follow-up imaging confirmed resolution of all lesions. CONCLUSION This case highlights that the aggressive and atypical presentation of disseminated melioidosis in T1DM may delay diagnosis. Persistent fever in endemic areas warrants prompt reevaluation. Early antibiotic escalation, timely surgical intervention, and multidisciplinary care were keys to recovery.